Effect of Dopants on Characteristics of Polypyrrole as a Liquid Crystal Alignment Layer - Kim, Y. C.; Kim, M. W.; Pak, S. S.; Kim, C. Y. (GORDON BREACH PUBLISHING, TAYLOR & FRANCIS GROUP, 1998)
Electrochemically polymerized polypyrrole (PPy) films with different dopants showed different surface energies. The films were used as alignment layers of liquid crystal displays (LCDs). The PPy films doped with ClO4- (PPy/ClO4) and PF6- (PPy/PF6) showed surface energies of 43.2 and 32.3 mJ/m2, respectively, while the pretilt angles of 4-cyano-4'-pentylbiphenyl on the films were 5.6 +/- 0.3 and 14.0 +/- 2.2 degrees, respectively. The electro-optic response time measured by light transmittance through the twisted nematic(TN) LCDs on switch-on was shorter for the display with PPy/PF6 than for that with PPy/ClO4. However, the turn-off response time was shorter for the display with PPy/ClO4 than for that with PPy/PF6. The total response time, which is the sum of the turn-on and turn-off response times, was 75 and 120 msec at 3.0 Vpp for the displays with PPy/ClO4 and PPy/PF6, respectively.